Penderitaan sebagai Pengalaman Eksistensial dalam Konsep Manusia Partisipan Menurut Gabriel Marcel: Suffering as an Existential Experience in the Concept of Participatory Humanity According to Gabriel Marcel - Turut, Yonesmus Rikardus; Riyanto, F. X. E. Armada (Undiksha, 2025)
The focus of this paper is to explore Gabriel Marcel's thinking on suffering as an existential experience that involves human participation in facing the realities of life. Suffering is often seen as a painful and destructive burden in human life, yet in Marcel's view, suffering is not merely a problem to be solved, but a